From Remote Control to Collaboration: Conducting NGO Research at a Distance in Tajikistan. Issue 2 (3rd April 2019) - Myrttinen, Henri; Mastonshoeva, Subhiya
ABSTRACT: Using a domestic violence-prevention project in Tajikistan as an example, we examine how international non-governmental organisations' (NGOs) knowledge production-at-a-distance, working through in-country teams who in turn rely on their local brokers, raises questions around ownership, power and privilege. These include issues around language and translation; motivations and agendas; and the neo-coloniality of data extraction and analysis. Yet, long-distance approaches can also have an emancipatory dynamic, leading to new forms of coproducing knowledge, although the frameworks for this continue to be deﬁned by the Global North, even if the categories of 'Global North' and 'Global South' are becoming increasingly blurred.